Moving Multicultural Education Forward in Teacher Education: Integration of Cognitive Learning Theory - Alvarado, Jose Luis; Pang, Valerie Ooka; Finley, Easter (Educational (Re)naissance, 2014)
Multicultural Education as a field of study in education is intimately connected to Teacher Education. Most frameworks in Multicultural Education are primarily centered on the inclusion of cultural and linguistic diversity in the curriculum of schools. The purpose of this article is to explain why cognitive learning theory must be an essential element in frameworks of Multicultural Education and Multicultural Teacher Education. Teachers need to understand the principles of cognitive development in students in order to create classrooms where students become self-regulated learners.